2020
DOI: 10.1039/c9ra07542a
|View full text |Cite
|
Sign up to set email alerts
|

The preparation of a modified PVDF hollow fiber membrane by coating with multiwalled carbon nanotubes for high antifouling performance

Abstract: In this study, an outer surface modified polyvinylidene fluoride (PVDF) hollow fiber membrane (HF-PVDF-CNT) was prepared by coating with dopamine (PD) and multiwalled carbon nanotubes (CNTs), to solve the problems of the instability of pure CNT mats fabricated by filter coating methods and membrane fouling in wastewater treatment. The modified membrane was assessed and characterized by various methods, including studies of its top surface and cross-sectional morphology, wettability, functional groups and elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…They were related with the benzene ring or N-H structure, carbonyl, and the amino groups or carboxyl groups, which proves that the HF-PVDF membrane were modied successfully by carbon nanotubes and dopamine. 26 However, for the used membrane, the strong absorbances at 3200 cm À1 , were attributed to the telescopic vibration peak of O-H in the hydroxyl groups, and the C-H telescopic vibration peak was appeared at 2900 cm À1 . 29 The materials had strong correlation peaks for absorption, such as 1652 and 1540 cm À1 , caused by amide band I and II, respectively.…”
Section: Organic Pollutants On the Membranementioning
confidence: 94%
See 1 more Smart Citation
“…They were related with the benzene ring or N-H structure, carbonyl, and the amino groups or carboxyl groups, which proves that the HF-PVDF membrane were modied successfully by carbon nanotubes and dopamine. 26 However, for the used membrane, the strong absorbances at 3200 cm À1 , were attributed to the telescopic vibration peak of O-H in the hydroxyl groups, and the C-H telescopic vibration peak was appeared at 2900 cm À1 . 29 The materials had strong correlation peaks for absorption, such as 1652 and 1540 cm À1 , caused by amide band I and II, respectively.…”
Section: Organic Pollutants On the Membranementioning
confidence: 94%
“…HF-PVDF-CNT membranes were fabricated by filtration coating, and the prepared procedures in detail were the same as our previous research. 26 The experimental bioreactor setup is shown in Fig. S1, † similar to the AnEMBR setup constructed by Katuri et al 19 But in our AnEMBR system, the cylindrical carbon-graphite felt containing a platinum core adhered strongly anaerobic sludge was used as the anode, and the HF-PVDF-CNT membrane module (contained HF-PVDF-CNT 10 membrane wires) was used as cathode.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that the electrochemically assisted membrane process experienced very little organic fouling during the long-term treatment of anaerobic reactor effluent. 260,261 The enhanced antifouling performance was attributed to the in situ membrane cleaning. 147,262 The H 2 and O 2 microbubbles generated from water electrolysis also reduced membrane fouling by preventing the formation of a cake layer.…”
Section: Electrochemical Fouling Mitigation Fouling Monitoring and Re...mentioning
confidence: 99%
“…The polar phases of PVDF can be produced by applying external field, such as high pressure, [5][6][7] mechanical stretching, [8][9] and high-voltage electrostatic field [10][11][12] or by the intermolecular interaction between the additives and PVDF, [13] among which adding additives proves to be the most convenient and effective preparation method. It has been reported that the addition of inorganic additives such as nanoclay, [14,15] BaTiO 3, [16,17] potassium bromide (KBr), [18] molybdenum disulfide (MoS 2 ), [19,20] zinc oxide (ZnO), [21,22] graphene, [23][24][25] and carbon nanotube [26][27][28][29] can boost the electroactive phases of PVDF mainly through the electrostatic interaction between the charged surface and the CH 2 or CF 2 dipoles of PVDF. However, the nano-scale dispersion of these solid fillers poses significant challenges for industrial fields.…”
Section: Doi: 101002/macp202100416mentioning
confidence: 99%